Dual-emitting Cu-doped ZnSe/CdSe nanocrystals - Sutton, Rebecca Suzanne (Kansas State University, 2015)
Cu-doped ZnSe/CdSe core/shell nanocrystals were synthesized using the growth doping method. Upon shell growth, the nanocrystals exhibit dual emission. The green luminescence peak is assigned as band edge emission and the broad, lower energy red peak is due to Cu dopant. Although, the oxidation state of Cu in the nanocrystals is debated, the emission is explained as recombination of a hole related to Cu²⁺ with an electron from the conduction band. The emission changed in the presence of dodecanethiol. Generally, the band edge emission intensity decreases and the Cu emission intensity increases. One explanation is the thiol acts as a hole trap, preventing hole transfer to the conduction band. Samples were obtained with varying amounts of Cd²⁺. In the presence of larger amounts of Cd²⁺, the nanocrystals had “thicker shells”, and both the band edge and Cu emission were less sensitive to thiol. The sensitivity likely decreased because the shelled, larger nanocrystals have fewer surface defects resulting in more available electrons.
Keywords: Cu-doped; Nano; ZnSe/CdSe; Core/shell nanocrystals; Chemistry (0485); Nanoscience (0565); Nanotechnology (0652)